Visible light photocatalytic mineralization of 17α-ethinyl estradiol (EE2) and hydrogen evolution over silver and strontium modified TiO2 nanoparticles: mechanisms and phytotoxicity assessment. Issue 8 (24th January 2018) - Wei, Xueyu; Li, Jie; Liu, Zhigang; Yang, Xiaofan; Naraginti, Saraschandra; Xu, Xiaoping; Wang, Xiaoju
Abstract : This study focusses on the novel synthesis of silver and strontium modified TiO2 nanocomposite through a sol–gel method, which was then utilized for visible light degradation of EE2 and hydrogen production for the first time. Abstract : This study focusses on the novel synthesis of silver and strontium modified TiO2 nanocomposite through a sol–gel method, which was then utilized for visible light degradation of EE2 and hydrogen production for the first time. Results indicated that co-doping of strontium and silver in the lattice of TiO2 could remarkably narrow the band gap (2.89 eV) for efficient visible light activity, as indicated by UV-DRS, PL and photocurrent experiment results. The obtained nanocomposite was further characterized by various techniques including XRD, TEM, and XPS analysis. Furthermore, the well characterized photocatalyst was investigated for the photocatalytic hydrogen evolution under visible light irradiation. The hydrogen production rate of double atom doped TiO2 (Sr/Ag–TiO2, 49.4 μmol h −1 ) is 2.6 times higher than that of single atom dopant (Ag–TiO2, 19.6 μmol h −1 ) nanocomposite. The plausible degradation pathway of EE2 during the photocatalytic process was investigated by LC-ESI/MS analysis. Additionally, to understand the toxicity of degraded metabolites and EE2, phytotoxicity testing was carried out on two common seeds, V. radiata and P. vulgaris ., and 30% and 40% germination rate was noticed for seeds exposed to 50 ppm concentration of EE2 in V. radiata and P. vulgaris respectively, while 100% was noticed in seeds exposed to degraded metabolites, which revealed the less toxic nature of degraded metabolites compared to pure EE2. In addition, substantial growth rate was also observed in the roots and shoots of the seeds treated with the degraded metabolites compared to pure EE2. Therefore, the present study demonstrates the detoxification of EE2 and evolution of hydrogen under visible light, and would greatly help in evaluation and extenuation of the environmental risk of EE2 for water reuse and the generation of clean energy.